2018
DOI: 10.1101/298240
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A 3D Topographical Model of Parenchymal Infiltration and Perivascular Invasion in Glioblastoma

Abstract: Glioblastoma (GBM) is the most common and invasive primary brain cancer. GBM tumors are characterized by diffuse infiltration, with tumor cells invading slowly through the hyaluronic acid (HA)-rich parenchyma toward vascular beds and then migrating rapidly along microvasculature. Progress in understanding local infiltration, vascular homing, and perivascular invasion is limited by an absence of culture models that recapitulate these hallmark processes. Here we introduce a platform for GBM invasion consisting o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…1G). We have previously demonstrated that U-87 MG cells invade HA-RGD by tunneling into the bulk matrix over the course of several weeks and that invasion is preceded by elaboration of long protrusions (37). We observe here that U-251 MG tumorspheres cultured in HA for 10 d exhibit protrusions into the matrix and initial tunneling (SI Appendix, Fig.…”
Section: Gbm Cell Adhesion and Migration On Ha Are Associated Withsupporting
confidence: 57%
“…1G). We have previously demonstrated that U-87 MG cells invade HA-RGD by tunneling into the bulk matrix over the course of several weeks and that invasion is preceded by elaboration of long protrusions (37). We observe here that U-251 MG tumorspheres cultured in HA for 10 d exhibit protrusions into the matrix and initial tunneling (SI Appendix, Fig.…”
Section: Gbm Cell Adhesion and Migration On Ha Are Associated Withsupporting
confidence: 57%
“…119,120 The contributions of the perivascular niche to therapy resistance, infiltration spread and disease progression are perhaps best understood. 83,118,[122][123][124] In the perivascular niche, GSCs and the TME engage in cooperative signalling, promoting neovascularization and GSC maintenance. The leaky vasculature provides access to nutrients, and the endothelium activates Notch-dependent pathways that promote GSC self-renewal and therapy resistance.…”
Section: Glioblastoma Stem Cell Nichesmentioning
confidence: 99%
“…Interestingly, dimensionality alone can profoundly affect cell responses to chemotherapeutics, independent of matrix stiffness or composition. 181 Materials used for 2D substrates, such as collagen 181,[186][187][188][189][190] and HA 123,183 , can also be employed as 3D scaffolds. However, materials such as polyacrylamide or polycaprolactone (PCL) requiring harsh solvents or crosslinking reagents during gelation cannot be easily seeded with cells unless they are made highly porous such that cells can be incorporated into the matrix after gelation.…”
Section: D Matrix Modelsmentioning
confidence: 99%
“…We also studied the impact of RGD incorporated in HA hydrogels as RGD is the key integrin‐binding sequence in fibronectin, which is enriched in the ECM of GBM tumors when compared to normal brain tissue (Kim & Kumar, ). Previously, RGD has been associated with increased adhesion and invasion of GBM cells in matrix‐free TCPS as well as 3D HA matrix (Paolillo, Serra, & Schinelli, ; Wolf, Lee, & Kumar, ; Xiao et al, ). In our system, apart from serum grown U87 cells, we observed no significant difference in the cell expansion, proliferation, and sphere sizes of serum‐free grown cells when incorporated in HA‐RGD hydrogels as compared with HA only hydrogels.…”
Section: Discussionmentioning
confidence: 97%